Multilateral Developing-Country Debt Rescheduling Negotiations : A Bargaining-Theoretic. (IMF Working Papers; Working Paper ;, 1988)
This paper employs a dynamic bargaining-theoretic framework to analyze multilateral sovereign debt rescheduling negotiations. The analysis illustrates how various factors, such as the debtor's gains from trade and the level of world interest rates, affect the relative bargaining power of various parties to a rescheduling agreement. If creditor-country taxpayers have a vested interest in maintaining normal levels of trade with debtor countries, then they can sometimes be bargained into making sidepayments. The benefits from unanticipated creditor-country sidepayments accrue to both lenders and borrowers. But the benefits from perfectly anticipated sidepayments accrue entirely to borrowers.